Functional analyses of the Terminal Ear 1-like RNA binding proteins of Arabidopsis thaliana : a thesis presented in partial fulfillment of the requirements of the degree of Doctorate of Philosophy in Plant Biology at Massey University, Palmerston North, New Zealand - Trainor, Vernon (Massey University, 2007)
In the Shoot Apical Meristem (SAM) the position at which leaf primordia arise on the periphery, and their subsequent differentiation, have been shown to be (at least in part) to be directed by genetic programs of development. A candidate gene associated with this regulation is TERMINAL EAR 1 (TE 1) a maize gene identified by the irregular phyllotaxy of its mutant lines. Unlike most other genes associated with meristem function, TE 1 is a novel RNA binding gene of the RRM type. It has been shown to have orthologues in a variety of plants including Arabidopsis thaliana as well as unicellular eukaryotes including MEI2, a gene whose product is associated with the regulation of meiosis in Schizosaccharomyces pombe. In order to more fully understand TE1's role, a functional characterisation of two of the so-called Mei2-like genes was undertaken in the model plant A. thaliana. These genes are called Terminal Ear-Like 1 and 2 (TEL1 and TEL2). Constitutive overexpression of the cDNA of TEL2 using the Cauliflower Mosaic Virus 35S promoter (CaMV35S) revealed a phenotype involving an apparently prolonged vegetative phase. However this was only observed in a limited number of lines of the total screened, and the next generation did not reiterate this phenotype. These difficulties were overcome using the LhGpOP construct system for ectopic misexpression in specific domains as well as inducible ubiquitous expression. Ectopic expression of either TEL cDNA is shown to lead to a pleiotrophic spectrum of phenotypes, which in general, were associated with reduced determinant development outside the apical meristems and as well as a delayed overall developmental progression. This provided some evidence that the normal function of TEL genes within the apical meristems is the repression of differentiation associated with the regulation of plant growth and architecture.
Keywords: Maize gene; Gene expression; Fields of Research::270000 Biological Sciences::270200 Genetics::270201 Gene expression